Measurement of right pulmonary artery diameter in normal chest radiographs - Bogati, Sabina; Maharjan, Surendra; Chand, Ram Bahadur (Journal of Chitwan Medical College, 2018)
Introduction: Many pathological condition and hypertension can be diagnosed by the measurement of the pulmonary artery. Our main objective was to measure the diameter of right pulmonary artery in normal chest radiographs. Methods: A cross-sectional study was performed in which, a total of 113 cases of chest radiographs were selected from July to October 2014, performed by qualified radiographer and reported by the radiologist. Right pulmonary artery is measured in Computed Radiography (CR) computer console. Obtained data were analyzed using in SPSS software version 20. Results: Among 113 cases, 52.2 % were male and 47.8 % were female. The mean diameter of the right pulmonary artery was found to be 11.96±2.04 mm, where in male, it was found to be 12.41 ± 2.0 mm and in female, it was found to be 11.46 ± 1.9 mm. The diameter of pulmonary artery was not correlated with height, weight, and BMI at 5% level of significance. Conclusion: This showed that female have narrower right pulmonary artery diameter than male. There was no significant relationship between pulmonary artery diameter and the height, weight and BMI. There was also no variation of measurement between male and female patients.